Diversity and interactions of bacteria from Laguncularia racemosa phylloplane - Moitinho, Marta Alves (2020)
Mangroves are dynamic ecosystems, which provide important ecological services to coastal areas due to the high rates of primary production and harbor several marine organisms . They are composed by a salinity tolerant vegetation that thrives in tropical and subtropical regions of the world under tidal influence. Plants broadly influence the ambient by means of photosynthesis and their leaves are responsible for a great part of the energy and organic matter input into planet Earth. Healthy plants in nature live in association and actively interact with a multitude of microorganisms belonging to several microbial types, collectively called the plant microbiota. Tropical ecosystems harbor a great epiphytic bacteria diversity with the potential to house new bacteria species, but most of the epiphytic microorganisms are uncultivated under commonly laboratory conditions when compared to other environments and little is known about the epiphytic bacterial diversity on mangrove habitats. Bacterial community structure of Laguncularia racemosa phylloplane, a well-adapted mangrove species with salt exudation at foliar levels, was accessed through 16S rRNA amplicon sequencing. Sampling was performed in three different sites across a transect from upland to the seashore in a preserved mangrove forest located in the city of Cananéia, São Paulo state, Brazil. Higher bacteria diversity was observed in intermediary locations between the upland to the seashore, showing that exists significant intraspecific spatial variation in bacteria communities between a single host species with the selection of specific population between an environmental transect. Bacteria reside in complex interactive communities in close association with competitors and partners. Microbial communities are dynamic and their structuration are determined by the pairwise interactions that occur between different species. Therefore, microbial cells exhibit intercellular communication and are aware of other cells in their vicinity, producing coordinated responses. In this work we also evaluated the multispecies interactions among ten strains isolated from Laguncularia racemosa phylloplane. All the strains had their growth diameter measured when growing in monocultures compared against their own growth in the pairwise interactions and in the consortium of three bacteria. In the total, fifteen consortia showed significant differences in the growth diameter of the bacteria in at least one combination. However, twenty-one consortia combinations did not show significant differences in the bacteria growth while interacting. In conclusion this work has showed that bacteria from L. racemosa phylloplane can sense other strains nearby and alter their rates of growth in response to the co-cultures.